Single-crystal field-effect transistors based on organic selenium-containing semiconductor - Zeis, Roswitha; Kloc, Christian; Takimiya, Kazuo; Kunugi, Yoshihito; Konda, Yasushi; Niihara, Naoto; Otsubo, Tetsuo (Japanese Journal of Applied Physics, 2005)
We report on the fabrication and characterization of single-crystal field-effect transistors (FETs) based on 2,6-diphenylbenzo[1,2-b:4,5-b′]diselenophene (DPh-BDSe). These organic field-effect transistors (OFETs) function as p-channel accumulation-mode devices. At room temperature, for the best devices, the threshold voltage is less than -7 V and charge carrier mobility is nearly gate bias independent, ranging from 1 to 1.5 cm2/(V s) depending on the source-drain bias. Mobility is increased slightly by cooling below room temperature and decreases below 280 K. © 2005 The Japan Society of Applied Physics.
Created from Fastlane, Scopus look-up
Keywords: Field effect transistor; Mobility; Organic semiconductor; Organic single crystal